Downregulated PTEN and aberrant JAK–STAT signal pathway in essential thrombocythemia patients - Luo, Lin; Liu, Xiaoyan; Shen, Hui; Zhang, Hao; Shang, Yufeng; Zhang, Xian; Zhang, Donglei (Frontiers in Hematology, 2025)
BackgroundEssential thrombocythemia (ET) is one of the Philadelphia-negative (Ph−) classical myeloproliferative neoplasms (MPNs), characterized by increased megakaryocyte and platelet counts, as well as an increased risk of thrombo-hemorrhagic complications. The JAK2 V617F mutation is detected in 50%–60% of patients with ET and can drive ET occurrence through ligand-independent activation of the thrombopoietin (TPO) receptor, resulting in JAK/STAT pathway signaling. Phosphatase and tensin homolog (PTEN) has been found to be associated with many hematologic diseases, particularly in MPNs, and is involved in the JAK/STAT pathway. This study aimed to determine the role of PTEN in ET patients with the JAK2 V617F mutation.MethodsIn this study, we analyzed a series of 32 ET patients without treatment and 25 age- and sex-matched normal controls for the detection of PTEN expression and the STT motif phosphorylation of PTEN, as well as the expression patterns of STAT3 and STAT5 and their phosphorylated molecules (p-STAT3 and p-STAT5, respectively), in bone marrow mononuclear cells (BM-MNCs) by immunohistochemical (IHC) staining of bone marrow biopsies and Western blotting. Correlations between the PTEN expression and other clinical characteristics were also examined.ResultsThe results showed a downregulated PTEN expression in the BM-MNCs of patients with ET, as well as an elevated p-STAT3 expression and a decreased p-STAT5 expression. In addition, analysis in combination with clinical data demonstrated a negative correlation between the expression of PTEN and the patients’ age and platelet counts. In contrast, a positive correlation was detected between the expression of PTEN and the level of p-STAT5.ConclusionsThe results of this study suggest that aberrant PTEN expression and JAK/STAT pathway signaling might be involved in the onset of ET. Our findings could shed new light on the pathogenesis of and the treatment for ET.